Parental mediation of smartphone and social media activities to protect early adolescent children from online risks - Kendra Allison; Robin M. Dawson (International Journal of Adolescence and Youth)
Early adolescent children engage in Internet-based online activities on smartphones and social media, which may result in online risks, including sexual risks. Parental mediation to regulate accessed content and contacts on smartphones and social media may prevent risks. This exploratory, descriptive study investigated parental mediation with early adolescent children 11 to 14 years old. A sample of 102 parents completed a REDCap online or paper-based survey to measure active mediation, co-use, general restrictive mediation, content-specific restrictive mediation, and supervision in response to a pre-survey prompt regarding mediation they use to protect their early adolescent children from sexual risks online. IBM SPSS Statistics 22 were used to analyse parental mediation frequencies. Participants utilized active mediation to communicate about appropriate online activities and restrictive mediation to control accessed content and contacts. Participants infrequently co-used by being online with children or supervised online activities. Future research should explore barriers to co-viewing and supervision.